Marker-assisted Introgression of a Broad-spectrum Resistance Gene, Pi40 Improved Blast Resistance of Two Elite Rice (Oryza sativa L.) Cultivars of Turkey - Beser, N.; Del Valle, M.M.; Kim, S.M.; Vinarao, R.B.; Sürek, H.; Jena, K.K. (Sophia Publishing Group, Inc., 2016)
Rice blast, caused by Magnaporthe oryzae is the most serious fungal disease of cultivated rice (Oryza sativa). In serious disease infection, significant yield loss in japonica and indica rice occurs every year worldwide. Of the 100 blast resistance genes identified, majorities are race specific and resistance breaks down rapidly. However, the new resistance gene, Pi40 shows broad-spectrum resistance to blast races in many tropical and temperate rice growing countries including Turkey. In this study, the Pi40 gene was introgressed into two Turkish elite cultivars, Osmancik-97 and Halilbey, to improve with broad-spectrum durable blast resistance and high yield potential through marker-assisted backcross breeding. Advanced backcross lines (ABLs) of BC3F6 and BC4F6 generations were produced from the crosses of Osmancik-97 and Halilbey with the Pi40-donor line, IR83260-1-1-1-5-B-3-1-2-B. ABLs with homozygous Pi40 alleles were selected by foreground analysis using gene-specific CAPS DNA marker 9871.T7E2b. The two varieties were expressing high susceptibility to blast disease isolates in Turkey and Philippines. Eleven selected ABLs expressed strong resistance to blast races in natural field and spray inoculation conditions. Background analysis of selected ABLs with 6K SNP assays showed 90.07% and 70.78% recovery of the recurrent genotype for Osmancik-97 and Halilbey ABLs respectively. We have produced valuable resources for blast disease resistance and developed improved breeding lines with strong resistance to blast for their cultivation in Turkey. Our new strategy of transferring the novel blast resistance gene (Pi40) into Turkish varieties will enhance rice production and productivity in the temperate regions of the world